On the Riesz basisness of the root functions of the nonself-adjoint Sturm-Liouville operator - (:unkn) unknown (MAGNES PRESS, 2005)
In this article we obtain the asymptotic formulas for eigenfunctions and eigenvalues of the nonself-adjoint Sturm-Liouville operators with periodic and antiperiodic boundary conditions, when the potential is an arbitrary summable complex-valued function. Then using these asymptotic formulas, we find the conditions on Fourier coefficients of the potential for which the eigenfunctions and associated functions of these operators form a Riesz basis in L-2(0, 1).